Die inklusiven Sprache(n) der sozialen Nachhaltigkeit: Deutsch und Italienisch im Vergleich - Crestani, Valentina; Brambilla, Marina (Linguistik Online, 2024)
This thematic issue collects a selection of the linguistic papers presented during the interdisciplinary conference Parità, genere, disabilità: la prospettiva giuridica e la prospettiva lingui-stica (‘Equality, gender, disability: the legal and linguistic perspective’) held in October 2021 at the University of Milan. The papers deal with the inclusive languages of social sustainability, and in particular, six focus on the topic “language and gender” and one on “language and disability”, mainly in German and Italian and partly in other languages. Both topics are analysed in the standard language and/or in specific domains of use (i. e., legal communication and institutional communication).